Physical performance and glycemic control under SGLT-2-inhibitors in patients with type 2 diabetes and established atherosclerotic cardiovascular diseases or high cardiovascular risk (PUSH): Design of a 4-week prospective observational study - Frundi, Devine S.; Kettig, Eva; Popp, Lena Luise; Hoffman, Melanie; Dumartin, Marine; Hughes, Magali; Lamy, Edgar; Fru, Yvonne Joko Walburga; Bano, Arjola; Muka, Taulant; Wilhelm, Matthias (Frontiers in Cardiovascular Medicine, 2022)
Background Type 2 diabetes (T2D) is associated with limitation in physical performance. Results from animal studies report enhancement of physical performance in T2D rodents treated with sodium glucose cotransporter 2 inhibitors (SGLT2is). However, in human patients with T2D and established atherosclerotic cardiovascular disease (ASCVD) or high cardiovascular risk, the impact of guideline directed SGLT2i medication on physical performance has not been sufficiently examined. Objectives The main objectives of this study are thus firstly, to assess the changes in physical performance after 4 weeks of exercise therapy in patients with established ASCVD or high cardiovascular risk categorized into three groups according to their glycemic control at baseline. Secondly, to investigate the association of glycemic control at baseline and new guideline directed antidiabetic treatment (inadequate glycemic control and diabetes + new SGLT2i vs adequate glycemic control and diabetes vs no diabetes) with change in physical performance. Methods and design This is a four-week prospective observational study of 450 participants with established ASCVD or high cardiovascular risk with or without T2D and without previous SGLT2i medication undergoing exercise therapy during inpatient rehabilitation in a single center in Switzerland. Upon admission, participants are categorized into 3 groups of 150 participants each according to their glycemic control. Group I consisting of participants with inadequately controlled T2D defined as mean fasting plasma glucose (FPG) of ≥ 7 mmol/L, who are consequently administered new treatment with an SGLT2i. Group II comprises of participants with adequately controlled T2D with mean FPG of < 7 mmol/L requiring no antidiabetic medication change. Group III consists of participants with no diabetes and mean FPG of ≤ 5.5 mmol/L. Primary outcomes are 6-minute walk distance and rate of perceived exertion. Secondary outcomes are echocardiographic parameters (left ventricular mass index; global longitudinal strain average; end-diastolic volume), fatigue, muscle, metabolic and anthropometric measures. Ethics and dissemination This study is conducted in accordance with the Declaration of Helsinki with ethical approval from the Cantonal Ethical Commission of Bern, Switzerland. The results will be published in a peer-reviewed journal. The implementation and reporting will be according to the SPIRIT guidelines. Clinicaltrial.gov Identifier: NCT03422263.